Perbedaan Hasil Belajar IPS dengan Menggunakan Model Pembelajaran Pair Check dan Cooperative Script pada Siswa Kelas VIII SMP Negeri 41 Rejang Lebong - Elva Susanti Elva Susanti Elva Susanti; Isbandiyah I; Sarkowi Sarkowi (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2021)
This study aims to determine differences in ips learning outcomes using the pair check learning model and cooperative script in class VIII students at SMP Negeri 41 Rejang Lebong. The research method used in this research is pure experiment. The population is all grade VIII students of SMP Negeri 41 Rejang Lebong in the academic year 2020/2021. The research sample was taken by random sampling because each class had relatively the same abilities and opportunities. The data collected was then analyzed using SPSS 16. Based on the results of the research and discussion, it can be concluded that there are differences in the results of learning history using the Pair Check Model and Cooperative Script at SMP Negeri 41 Rejang Lebong, this can be seen from the results of the pre-test mean score in the class. Experiment 1 is 63.59 and in Experiment 2 class is 62.69. While the average value in the experimental class 1 after being given treatment using the Pair Check model was 87.31, and in the experimental class 2 which was given learning by the Discussion method was 71.67. Thus, it means that the average value of the experimental class 1 is greater than the experimental class 2.From the results of the data analysis using the Independent Sample T-test, the final test value is Sig. (2-tailed) = 0.000 <Sig = 0.05, then Ho is rejected, Ha is accepted. This means that the hypothesis proposed by Ho is rejected, Ha is accepted. So it can be concluded that there is a difference in the results of learning history using the Pair Check and Cooperative Script learning model in class VIII students at SMP Negeri 41 Rejang Lebong, which can be accepted as true.